How do coalitions stop pipelines? Conditions that affect strategic action mobilizations and their outcomes. (April 2023) - Hess, David J.; Kim, Yu-Ri; Belletto, Kaelee
Abstract: The study develops a strategic action perspective on public opposition to energy infrastructure by examining the conditions that lead to mobilization and conditions and actions that lead to a decision not to build a pipeline. Based on clearly defined inclusion criteria, fifty cases of proposed natural gas pipeline infrastructure in the U.S. were selected. Location within just one state is associated with a lower level of mobilization against a pipeline. In cases with higher opposition, the no-build outcome is associated with location in at least one state that leans toward the Democratic Party (more progressive), a higher level of tactics and more diverse coalitions, and pipeline opposition from state government officials. A processual model of the mobilization process, decision points, and outcomes is developed. Even with federal government approval, court decisions and state-government certification can create legal and regulatory hurdles that are associated with a no-build outcome. Given limited mobilization resources, opposition coalitions may benefit from strategic action focused on institutional targets of action such as the decisions of uncaptured regulatory agencies and the courts. The study also identifies incremental rule changes in these targets of action and the potential for improved democratic governance. Highlights: A strategic action perspective is developed and applied to show its value in the analysis of energy politics. A unique data set of proposed U.S. gas pipelines shows opposition in more than half of the cases. Contextual conditions are identified for the level of mobilization and no-build outcome. An analysis of tactics and coalition composition shows specific associations with a no-build outcome. In no-build cases, crucial decision-making units are identified, including the courts and subnational regulatory agencies.